OPINI PUBLIK TERHADAP AGROWISATA LEMBAH HIJAU MULTIFARM KABUPATEN SUKOHARJO - , NUR BRILLIYANTIN SOLIHAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the visitors and the public opinion about the âLembah Hijau Multifarmâ and determine the factors related to the formation of such opinion. The basic method used in this study is a descriptive analysis method. Sampling as many as 30 visitors and 30 surrounding communities conducted by purposive sampling and accidental sampling. Analysis of the data using the proportions test and Spearman rank correlation test. Opinion visitors measured by several indicators of conditions, facilities, services and accessibility while public opinion is measured through indicators of CSR, employment and environmental conditions. The results of this study indicate that the opinion of the âLembah Hijau Multifarmâ among visitors is positive, for example, visitors opinion of the condition, facilities and services. While the results of opinion among the people is negative, for example, public opinion towards CSR and employment. The experience of other visitors to ecotourism has a positive relationship in the formation of opinions, visitors who've been to other agro tends to give a positive opinion. Factors of age, education, income, occupation, place of origin, and knowledge does not have a significant relationship in the formation of opinion. Similarly for people age, education, income, occupation, residence distance, the experience, the presence of family members who work at the âLembah Hijau Multifarmâ and knowledge do not have a relationship in the formation of public opinion. Keywords: opinion, agrotourism